Synthesis and evaluation of ortho-[18F]fluorocelecoxib for COX-2 cholangiocarcinoma imaging - Chang CW; Yeh CN; Chung YH; Chen YR; Tien SW; Chen TW; Farn SS; Huang YC; Yu CS (Dove Medical Press, 2018)
Chi-Wei Chang,1,* Chun-Nan Yeh,2,* Yi-Hsiu Chung,3,* Yong-Ren Chen,4 Shi-Wei Tien,4 Tsung-Wen Chen,2 Shiou-Shiow Farn,4,5 Ying-Cheng Huang,6 Chung-Shan Yu4,7 1Department of Nuclear Medicine, Taipei Veterans General Hospital, Taipei, Taiwan; 2Department of Surgery, Liver Research Center, Chang-Gung Memorial Hospital at Linkou, Chang Gung University, Taoyuan, Taiwan; 3Center for Advanced Molecular Imaging and Translation, Chang Gung Memorial Hospital, Taoyuan, Taiwan; 4Department of Biomedical Engineering and Environmental Sciences, National Tsinghua University, Hsinchu, Taiwan; 5Isotope Application Division, Institute of Nuclear Energy Research, Taoyuan, Taiwan; 6Department of Neurosurgery, Chang-Gung Memorial Hospital at Linkou, Chang Gung University, Taoyuan, Taiwan; 7Institute of Nuclear Engineering and Science, National Tsinghua University, Hsinchu, Taiwan *These authors contributed equally to this work Background: An 18F-tagged NSAID analog was prepared for use as a probe for COX-2 expression, which is associated with tumor development. Methods: The in vivo uptake of celecoxib was monitored with ortho-[18F]fluorocelecoxib using positron emission tomography (PET). The binding affinity of ortho-[18F]fluorocelecoxib to COX-1 and COX-2 enzymes were assessed using the competitor celecoxib. Results: The IC50 values were 0.039 μM and 0.024 μM, respectively. A selectivity index of 1.63 was obtained (COX-2 vs COX-1). COX-2 overexpressed cholangiocarcinoma (CCA) murine cells took up more ortho-[18F]fluorocelecoxib than that by usual CCA cells from 10 to 60 minutes post incubation. Competitive inhibition (blocking) of the tracer uptake of ortho-[18F]fluorocelecoxib in the presence of celecoxib by the COX-2 overexpressed CCA cells and the usual CCA cells gave the IC50 values of 0.5 μM and 46.5 μM, respectively. Based on the in vitro accumulation data and in vivo metabolism half-life (30 min), PET scanning was performed 30–60 min after the administration of ortho-[18F]fluorocelecoxib through the tail vein. Study of ortho-[18F]F-celecoxib in the CCA rats showed a tumor to normal ratio (T/N) of 1.38±0.23 and uptake dose of 1.14±0.25 (%ID/g). Conclusion: The inferior in vivo blocking results of 1.48±0.20 (T/N) and 1.18±0.22 (%ID/g) suggests that the nonspecificity is associated with the complex role of peroxidase or the binding to carbonic anhydrase. Keywords: celecoxib, fluorination, imaging, NSAIDs, blocking, PET